Análise das preferências dos irrigantes por sistema de cobrança pelo uso da água bruta: o caso do perímetro irrigado de tabuleiro de Russas - Coutinho, Alisson Costa (2015)
The water management was established by National Water Resources Policy (NWRP), instituted by federal law n. 9.433/1997. Among the prescribed instruments for reaching the water policy purposes, it is the water charging. The sector with by far the largest water withdrawal is the irrigation. By the year 2013, the water charging for irrigation water users, in the state of Ceará, had been implemented in two Irrigation communities (Tabuleiro de Russas and Jaguaribe-Apodi) and in the irrigated area being developed over Canal do Trabalhador. Considering the existence of different irrigation water charging methods, the most appropriate method to the characteristics of the region and the users can promote water use efficiency in irrigation, as well as the equitable allocation of this resource. These different methods raise questions about its legal, economic, social and environmental implications. In this sense, the purpose of this research is to analyze the irrigator preferences, from Irrigation Community of Tabuleiro de Russas – Ceará by different water charging systems, considering the following attributes: water charging methods, water rights Market, amount of guaranteed water supply and different prices. This research uses the stated preference approach, called modeling choice. A random sampling was applied proportional to the number of blocks of choice sets. 30 questionnaires were applied to the owners or managers of production lots of Irrigation Community, randomly selected. The typical profile of irrigation user of lots classified as small producers is then characterized by a man, over 40 years old, married, with 02 or 03 children, with incomplete primary education, monthly income of one to three minimum wages, which visits lot daily. On assessment of the attitudes and behaviors of irrigators for the different attributes of water charging system, responses showed that irrigators recognize the importance of raw water charging. The producers’ relationship with the land is that it should produce, the water right speculation conduct is disapproved over the labor on land. Based on primary data, the results showed that irrigators prefer a water charging method that considers actual water consumption, determined by individualized hydrometers. The possibility of water rights market was chosen so associated with preference of an alternative way to the current scenario. The preference for amount of guaranteed water supply was due to water shortages experienced by the state and by the water rationing carried out on the Irrigated area. The chosen price means that irrigators recognize that the values practiced, generally, are low, thus, they prefer to remain with current values.